Pritiski in bolečina v stopalih ter sposobnost za hojo pri bolnikih z revmatoidnim artritisom - Novak, Primož (Rehabilitacija (Ljubljana), 2011)
Background: Rheumatoid arthritis can cause severe impairment in foot structure and consequently foot function (pain), which can lead to difficulties in patients' activity (walking). The purpose of our study was to measure plantar pressures and assess their association with forefoot pain and walking ability of rheumatoid arthritis patients. Methods: Sixty rheumatoid arthritis patients were included. Plantar pressure measurement was performed with the F-scan system. Pain subscale of the Foot Function Index was used for the assessment of foot pain. Walking ability was assessed by the 6-minute walking test. Results: Plantar pressures were significantly higher on average at painful than at non-painful foot areas. Foot pain is significantly associated with walking ability - walking distance increases as foot pain decreases. Multiple regression model confirmed pain to be an independent prognostic factor of walking ability when controlling for basic patient characteristics. Conclusion: Due to foot pain, rheumatoid arthritis patients have difficulties in walking. Foot pain is related to higher plantar pressures.
Keywords: bolečina; komplikacije; patofiziologija; poškodbe; rehabilitacija; revmatoidni artritis; stopalo; vocational rehabilitation